A Categorical Content Analysis of Highly Cited Literature Related to Trends and Issues in Special Education. (November 2018) - Arden, Sarah V.; Pentimonti, Jill M.; Cooray, Rochana; Jackson, Stephanie
This investigation employs categorical content analysis processes as a mechanism to examine trends and issues in a sampling of highly cited (100+) literature in special education journals. The authors had two goals: (a) broadly identifying trends across publication type, content area, and methodology and (b) specifically identifying articles with disaggregated outcomes for students with learning disabilities (LD). Content analyses were conducted across highly cited (100+) articles published during a 20-year period (1992–2013) in a sample ( n = 3) of journals focused primarily on LD, and in one broad, cross-categorical journal recognized for its impact in the field. Results indicated trends in the article type (i.e., commentary and position papers), content (i.e., reading and behavior), and methodology (i.e., small proportions of experimental and quasi-experimental designs). Results also revealed stability in the proportion of intervention research studies when compared to previous analyses and a decline in the proportion of those that disaggregated data specifically for students with LD.